Self-Determination as a Predictor of Career Decision-Making among Senior High School Students - Ismiati Ismiati; Juli Andriyani; Rofiqa Duri; Reza Muttaqin (Kuras Institute, 2026)
This study aims to analyze the relationship between self-determination and career decision-making ability among senior high school students. The research is grounded in a global and national context showing that many adolescents, including Indonesian high school graduates, continue to experience uncertainty in choosing a career path. The study was conducted with Grade XII students of SMA Negeri 3 Banda Aceh using a quantitative, correlational design. The population comprised 346 students, and a sample of 177 was selected through simple random sampling based on the Issac and Michael table with a 5% margin of error. Instruments included the Self-Determination Scale covering autonomy, competence, and relatedness—and the Career Decision-Making Scale, which measures the stages of exploration, crystallization, choice, and clarification. Content validity was examined using the Content Validity Ratio (CVR), while reliability was assessed with Cronbach’s alpha, yielding high coefficients (α self-determination = 0.871; α career decision-making = 0.867). The analysis revealed that most students demonstrated moderate levels of both self-determination and career decision-making ability. Pearson’s product–moment correlation produced a coefficient of r = 0.533 with p = 0.000 (p < 0.05), indicating a positive and highly significant relationship between self-determination and career decision-making. In other words, the higher the students’ autonomy, competence, and relatedness, the more mature their educational and occupational choices. This research underscores that fulfilling the basic psychological needs of autonomy, competence, and relatedness plays a crucial role in preparing students for the transition to higher education or the workforce. The findings recommend implementing school-based career guidance programs that foster intrinsic motivation, encouraging parental involvement to support adolescents’ exploratory freedom, and providing broader access to career information.